2011
DOI: 10.1253/circj.cj-11-0641
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown of the Intermediate-Term Fractal Scaling Exponent in Sinus Node Dysfunction - New Method for Non-Invasive Evaluation of Sinus Node Function -

Abstract: Circulation Journal Official Journal of the Japanese Circulation Society http://www. j-circ.or.jp inus node dysfunction (SND), also referred to as "sick sinus syndrome", is a common cause of cardiac syncope. 1 Sinus bradycardia (SB) is not only an incidental finding in otherwise healthy individuals, particularly in young adults, but also an electrocardiographic manifestation of SND. 2-5 Differentiation of so-called pathologic SB (due to intrinsic SND), from normal SB, is important in the diagnosis and manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Furthermore, Shin et al discovered that patients with sinus node dysfunction significantly reduced their DFA slope2 levels, indicating that diseased sinus node may break down long‐term fractal complexity (Shin et al, 2011 ). In our study, compared to pre‐PVI level, the DFA slope2 increased significantly 1–3 months and 6–12 months post‐PVI, in the non‐recurrence group, whereas there was only a significant increase between pre‐PVI and 1–3 months post‐PVI in the recurrence group.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Shin et al discovered that patients with sinus node dysfunction significantly reduced their DFA slope2 levels, indicating that diseased sinus node may break down long‐term fractal complexity (Shin et al, 2011 ). In our study, compared to pre‐PVI level, the DFA slope2 increased significantly 1–3 months and 6–12 months post‐PVI, in the non‐recurrence group, whereas there was only a significant increase between pre‐PVI and 1–3 months post‐PVI in the recurrence group.…”
Section: Discussionmentioning
confidence: 99%
“…However, we expected statistically significant changes in the value of this exponent both in responders and non-responders, especially since this is the only parameter that separated these two groups of patients at the baseline examination. Our results indicate that α 2 RR should not be considered only as an indicator of the state of ANS, i.e., the degree of blockade of the ß receptors but also as a marker of preservation of the function of the sinoatrial node cells [ 51 ]. In our study, in CRT non-responders, α 2 (RR) practically does not change, so the values of this parameter between responders and non-responders at the follow-up do not differ significantly due to the decrease in α 2 (RR) in CRT responders.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, it can be found that the increase in α 1 is usually related to vagal withdrawal (Tulppo et al, 2001; Castiglioni et al, 2011) but in this HF states probably with preserved feedback loops of regulatory mechanisms. Tendency to decreased α 2 in the fourth cluster may be related to sinus node dysfunction (Shin et al, 2011) or the β-receptor blockade (Castiglioni et al, 2011). It is believed that complexity of interbeat interval fluctuations is generated solely by ANS activity and that quantified linear and non-linear parameters of HRV are quantifiers of modulatory mechanisms of ANS.…”
Section: Discussionmentioning
confidence: 99%
“…Hotta et al (2005) showed that α 2 is a more powerful measure for predicting cardiac morbidity and mortality. In the study of Shin et al (2011) long-term scaling exponent was the only parameter which was capable of discriminating differences in heart rate dynamics between patients with sinus node dysfunction. They concluded that reduced value of α 2 is a robust measure and could be an adjunctive tool for improvement of diagnostic performance in detection of sinus node dysfunction.…”
Section: Discussionmentioning
confidence: 99%